Histomorphometric Evaluation of Superovulation Effect on Follicular Development after Autologous Ovarian Transplantation in Mice - Amin Tamadon; Alireza Raayat Jahromi; Farhad Rahmanifar; Mohammad Ayaseh; Omid Koohi-Hosseinabadi; Reza Moghiminasr (Veterinary Medicine International)
The effect of superovulation by pregnant mare serum gonadotropin (PMSG) on autologous transplanted ovaries in the lumbar muscles of mice was histomorphometrically evaluated using the indices of number and volume of different kind of follicles and volume of corpora lutea, ovary, and stroma. Angiogenesis was observed after mouse ovarian transplantation on days 14 and 21 after ovarian grafting. After transplantation, the total number and volume of primary and secondary follicles reduced, while PMSG superovulation increased the total number and total volume of tertiary follicles and also the ovarian volume after transplantation. Transplantation increased the average size of primary, secondary, and tertiary follicles. Therefore, primary and secondary follicles can survive after autologous transplantation but their reservations diminished by increasing the time of transplantation. However, number of tertiary follicles and their response to superovulation increased over time after transplantation.